Sistem Informasi Data Kependudukan DesaWee Rame Berbasis Web - David Dairo Bio; Elfira Umar; Agustina Purnami Setiawi (CV. ITTC INDONESIA, 2023)
Always evolves population information system is needed to community service.Population information valid the data recorded in clusters bottom in this is a village.Until now, information systems village wee rame still both manual way in public services of population.Village officials mnginput population data not use application and less effective and efficient in data processing the information.Storage file heaped has created problems and inadequate storage space.Penggunakaan applications in this case is desa-desa population and information system is needed to the saving of time and energy, and increase the quality of public services.Population information system web based this village, designed and constructed using laravel mysql and to the databases.The trial is to ensured a valid of processing